Cortical astrocytes develop in a plastic manner at both clonal and cellular levels - Solène Clavreul (Nature Portfolio, 2019)
Previous studies on astrocyte development have led to controversial results due to a lack of pertinent tools. Here, authors analyze large numbers of astrocyte clones generated by nearby cortical progenitors using the MAGIC Markers strategy and ChroMS 3D imaging, and show that clonally-related astrocytes organize in a non-stereotyped manner and that cortical astrocyte subtypes are not intrinsically specified.